Dietary Reversal Ameliorates Short- and Long-Term Memory Deficits Induced by High-fat Diet Early in Life - Sims-Robinson, Catrina (PLoS One, 2016)
A high-fat diet (HFD), one of the major factors contributing to metabolic syndrome, which is associated with an increased risk of neurodegenerative diseases, leads to insulin resistance and cognitive impairment. It is not known whether these alterations are improved with dietary intervention. To investigate the long-term impact of a HFD on hippocampal insulin signaling and memory, C57BL6 mice were placed into one of three groups based on the diet: a standard diet (control), a HFD, or a HFD for 16 weeks and then the standard diet for 8 weeks (HF(16)). HFD-induced impairments in glucose tolerance and hippocampal insulin signaling occurred concurrently with deficits in both short- and long-term memory. Furthermore, these conditions were improved with dietary intervention; however, the HFD-induced decrease in insulin receptor expression in the hippocampus was not altered with dietary intervention. Our results demonstrate that memory deficits due to the consumption of a HFD at an early age are reversible.